UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS X.E1 SMA NEGERI 6 DENPASAR TAHUN PELAJARAN 2023/2024 - I Wayan Pebri Muliatmika; I Komang Sukendra; I Wayan Suwiasa (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Teachers employ various methods for classroom instruction, but achieving optimal results remains challenging. Recognizing the need for innovation, this study focuses on implementing the Problem Based Learning (PBL) model to enhance mathematical learning outcomes, particularly in Trigonometry for class X.E1 at SMA Negeri 6 Denpasar during the 2023/2024 academic year. The two-cycle class action research reveals improved outcomes, demonstrating that the application of the PBL model leads to enhanced results and identifies sequential steps for implementation. The research, utilizing a class action methodology, involves students from class X.E1 during the academic year 2023/2024. The study emphasizes Trigonometry outcomes, employing the PBL model in two cycles, including initial reflection, action planning, implementation, observation/data collection, and reflection. Data, collected through observation and written tests using instruments such as observation sheets and descriptive questions, undergoes descriptive analysis. The findings underscore the efficacy of the PBL model in improving mathematics learning outcomes, offering insights into its application for Trigonometry in the specific context of class X.E1 at SMA Negeri 6 Denpasar during the first semester